Rice (Oryza sativa) cultivars suitable for anaerobic seeding - SARKAR, R K; BERA, S K; DE, R N (The Indian Journal of Agricultural Sciences, 2013)
An experiment was conducted during 1995 to develop cultivars suitable for direct anaerobic seeding technology, ie germinated seeds are to be shown beneath the surface of flooded soil. For anaerobic direct wet seeding the genotype; ’CH 19’ rice (Oryza sativa L.) was found to be better followed by ’T 1471’ and ’FR 13A’. These genotypes could be utilized as parents In breeding programmes. Direct sowing with nOn-germinated seeds under anaerobic condition is observed to be illusive.